A novel application of salivary testosterone in systolic heart failure: relationship with exercise capacity, quality of life and cardiac mechanics. Issue 1 (March 2015) - Stout, Martin; Pearce, Keith; Williams, Simon G.
Abstract : Introduction: There is an association between heart failure (HF) and testosterone deficiency. Salivary testosterone (ST) has been described as a marker of the free fraction of testosterone in healthy populations and has not commonly been utilized clinically. This study aimed to assess the clinical utility of ST in a HF population with a broad range of testosterone concentrations compared with more traditional serum parameters. Methods: A total of 40 men with HF were recruited. Traditional serum testosterone measures and ST measures were collected on two separate occasions. Patients performed a 6-min walk, underwent echocardiography and completed quality of life questionnaires. Bland–Altman plots were constructed to assess the agreement between ST and free testosterone (FT) levels, and to assess the repeatability between traditional and ST measures. Pearson's correlation was used to determine the relationship between ST levels, traditional serum testosterone parameters and important health outcomes. Results: There was excellent agreement between ST and FT measures [bias 0.087 nmol/l, SD 0.056 nmol/l, 95% limits of agreement (LoA) of +2 SD 0.104 nmol/l and −2 SD −0.122 nmol/l]. ST and FT measures show excellent reproducibility (bias 0.0137 nmol/l, SD 0.021 nmol/l, 95% LoA +2 SD 0.041 nmol/l and −2 SD −0.041 nmol/l for ST, and bias 0.004 nmol/l, SD ±0.0025 nmol/l, 95% LoA ±2 SD +0.055 nmol/l and −0.046 nmol/l). There are similar levels of moderately strong positive correlation between ST levels, other testosterone fractions and endurance capacity/physical domains of quality of life assessed using the Short Form-36 questionnaire. Conclusion: ST can be used as an alternative marker of traditional testosterone parameters in HF without semi-invasive blood sampling. There is a correlation between exercise capacity and physical quality of life domains with all testosterone fractions.